Analisis Kemampuan Pemahaman Pembelajaran IPS Pada Peserta Didik Kelas IX SMP Negeri 1 Bakongan Timur Aceh Selatan - Junaidi Junaidi; Julia Ivanna (FKIP, Universitas Palangka Raya, 2022)
The problem that often occurs is that many students are still less interested in studying social studies learning, because students feel that social studies learning is only a boring story. Then the formulation of the problem studied is how the knowledge of social studies learning of students in Class IX SMP Negeri 1 Bakongan Timur Selatan. The purpose of the study was to determine the understanding of social studies learning by students in Class IX of SMP Negeri 1 Bakongan Timur. The research method used is quantitative research method, with data collection techniques using questionnaires and documentation. The result of the research is that the understanding of Class IX students of SMP Negeri 1 Bakongan Timur in Social Science Learning (IPS) in 2021/2022 is included in the